Indo-European origin of alphabetic systems and deciphering of the Byblos script. Issue 3 (3rd July 2017) - Rassokha, Ihor
Abstract : The Irish alphabet Runogham and the Oghamic signs Forfeda are very similar to the ancient Indian Brahmi alphabet. Besides, a common origin with them have such alphabets as Phoenician, South Arabian, the Ancient Italic, Carpathian runes, Germanic runes, Aramaic, the Ancient Berber, Carian, Ugaritic and Old Permic. Possible "parent" system for all these writing systems is the Script of the Catacomb culture in South-Eastern Ukraine. A wide expansion of chariots from South-Eastern Ukraine during the Bronze Age can be considered as the reason for the expansion of the Catacomb writing system. A deciphering of the Byblos alphabetic script based on the Brahmi letters is made taking into account the data related to writing systems mentioned above. As the result a conclusion has been made that the Byblos texts should be read in Sanskrit. The total gift character of inscriptions in any case is fully consistent with artifacts on which they are made.